The intergenerational transmission of risk and trust attitudes - Thomas Dohmen; Armin Falk; David Huffman; Uwe Sunde (Institute for the Study of Labor (IZA), 2006)
We investigate whether two crucial determinants of economic decision making willingness to take risks and willingness to trust other people are transmitted from parents to children. Our evidence is based on survey questions that ask about these attitudes directly, and are good measures in the sense that they reliably predict actual risk-taking and trusting behavior in large-scale, incentive compatible field experiments. We find a strong, significant, and robust correlation between the responses of parents and their children. Exploring heterogeneity in the strength of transmission, we find that gender of the child does not matter, but that children with fewer siblings, and firstborn children, are more strongly influenced by parents in terms of risk attitudes. Interestingly, for trust there is no impact of family size or birth order. There is some evidence of 'receptive' types: children who are similar to the father are similar to the mother, and children who are similar to parents in terms of risk are similar in terms of trust. We find that the transmission from parents to children is relatively specific, judging by questions that ask about willingness to take risks in specific contexts financial matters, health, career, car driving, and leisure activities. Finally, we provide evidence of positive assortative mating based on risk and trust attitudes, which reinforces the impact of parents on children. Our results have potentially important implications for understanding the mechanisms underlying cultural transmission, social mobility, and persistent differences in behavior across countries. More generally, our findings shed light on the basic question of where attitudes towards risk and trust come from.
urn:nbn:de:101:1-20090406172
Keywords: 330; Meinung; Risikoaversion; Vertrauen; Familiensoziologie; Generationenbeziehungen; Eltern; Kinder; Deutschland